A critical review of Cu2SnS3 (CTS) thin films solar cells - Md. Fakhrul Islam; Puvaneswaran Chelvanathan; Mohammad Tanvirul Ferdaous; Mohd Azman Hashim@Ismail; Anup Kumar Modak; Nowshad Amin; Nadhrah Md Yatim (Penerbit USIM, Universiti Sains Islam Malaysia, 2024)
E-Proceeding Kolokium Siswazah Fakulti Sains Dan Teknologi 2020 (KOSIST 2020) “Synergizing Innovation and Research Through Science and Technology” 9th December 2020 Organized by Faculty Science and Technology